FALCIPARUM MALARIA - AN EXPERIENCE WITH 100 CASES - Gandapur, Abdus Salam Khan; Malik, Salman A,; Qayyum, Abdul; Khan, Misal (Journal of Ayub Medical College Abbottabad, 1995)
Clinical details and present day problems faced in 100 cases of Falciparum Malaria (FM) are reported. Eleven percent had taken chloroquine prior to reporting to us. The parasite density lacked correlation with the severity of disease. Pattern of fever varied markedly but 10% were afebrile throughout and presented only with body ache and malaise. Cerebral malaria was present in 117c patients. Jaundice was present in 187c patients. Other symptoms were vomiting 447c, severe headache 127c, pain abdomen 77c, loose motions/dysentery 117c, & cough 87c, while bleeding diathesis was present in 77c (3 meletia, 2 epistaxis, 1 bleeding gums and 1 haematuria). Severe anaemia was present in 107c of cases. Splenomegaly was present in 657c, hepatomegaly 297c and hepatosplenomegaly 217c. Congenital malaria was present in only one (17c) patient. Mild malaria patients were treated with chloroquine, while severe malaria patients were cured with quinine for 7 days. Blackwater fever was present in 27c.Patients with Blackwater fever were cured with steroids and chloroquine. 127c patients had chronic malaria. 837c of these patients presented with anaemia. Self-medication, haphazard therapy and the slogan "Fever May Be Malaria, Take Chloroquine" can lead to problems in Falciparum Malaria. Clinical immunity and parasite strain may act as virulence factors.